Chest Compression Rates of 90/min versus 180/min during Neonatal Cardiopulmonary Resuscitation: A Randomized Controlled Animal Trial - Marlies Bruckner; Mattias Neset; Catalina Garcia-Hidalgo; Tze-Fun Lee; Megan O'Reilly; Po-Yin Cheung; Georg M. Schmölzer (MDPI AG, 2022)
Background: To compare chest compression (CC) rates of 90/min with 180/min and their effect on the time to return of spontaneous circulation (ROSC), survival, hemodynamic, and respiratory parameters. We hypothesized that asphyxiated newborn piglets that received CC at 180/min vs. 90/min during cardiopulmonary resuscitation would have a shorter time to ROSC. Methods: Newborn piglets (n = 7/group) were anesthetized, intubated, instrumented and exposed to 45 min normocapnic hypoxia followed by asphyxia and cardiac arrest. Piglets were randomly allocated to a CC rate of 180/min or 90/min. CC was performed using an automated chest compression machine using CC superimposed with sustained inflation. Hemodynamic and respiratory parameters and applied compression force were continuously measured. Results: The mean (SD) time to ROSC was 91 (34) and 256 (97) s for CC rates of 180/min and 90/min, respectively (p = 0.08). The number of piglets that achieved ROSC was 7 (100%) and 5 (71%) with 180/min and 90/min CC rates, respectively (p = 0.46). Hemodynamic parameters (i.e., diastolic and mean blood pressure, carotid blood flow, stroke volume, end-diastolic volume, left ventricular contractile function) and respiratory parameters (i.e., minute ventilation, peak inflation and peak expiration flow) were all improved with a CC rate of 180/min. Conclusion: Time to ROSC and hemodynamic and respiratory parameters were not statistical significant different between CC rates of 90/min and 180/min. Higher CC rates during neonatal resuscitation warrant further investigation.